STREET VIOLENCE AND ITS EFFECTS IN SOCIAL SPACE (Religious dialogue and cooperation, 2023)
The issue of violent manifestations in different social environments such asstreet, school or family constitutes a priority and a fundamental field, both for scientificresearch and for the intervention of competent institutions and personnel, in the contextof contemporary societies, including the Romanian social space. Streets are a spacefor manifestations of violence that propagate in different registers. Deviant behaviouramong students and, at the same time, among other categories of participants in educationaland instructive activities significantly affects the school institution. In contrastto other social spaces, the school requires an immediate, appropriate, and particularlyprofessional response.
Keywords: students; school violence; terrorism; deviant behavior